Ghosts of Kanungu : fertility, secrecy & exchange in the Great Lakes of East Africa - Vokes, Richard (African anthropology., 2009)
On 17 March 2000 several hundred members of a charismatic Christian sect, the Movement for the Restoration of the Ten Commandments of God (MRTC), burnt to death in the group's headquarters in the Southwest Ugandan village of Kanungu. Days later the Uganda.